The Effect of Ionic Substitution on the E.P. of Superconductor using Madelung Method - Bassam Mustafa (College of Education for Pure Sciences, 2009)
Abstract The effect of substitution of the ion instead of La+3 in the superconductor was studied, an increase in electrostatic potential energy E. P. (E) with increase of Sr % was noticed, and a step change in P. E. when Sr is added is noticed indicating a phase change occurrence in the crystal structure .Increase of Tc, with the increase of Sr, noticed earlier, is linked with increase of E.P. and a relation between E.P. and Tc is found , the increase of Tc is due the creation of holes by valance difference between La & Sr, which also leads to collapse of crystal by reduction of repulsion between Sr & Cu atoms this have the same effect as the application of pressure on the crystal, which increases Tc also. For x >0.15, Tc decreases due to the appearance of vacancies which may have screening effect of the electrostatic field.